Enhancing Perioperative Patient Safety: A Collective Responsibility - Laflamme, Lynne (Operating Room Nurses Association of Canada Journal, 2017)
Teamwork, patient advocacy, and high quality safe care are at the core of the perioperative nursing profession. Although perioperative health professionals endeavour to provide high quality and safe patient care the prevalence of preventable adverse events (AEs) in the perioperative setting reflects an emergent need to improve perioperative patient safety. Remarkably, studies related to preventable AEs consistently describe teamwork challenges to be responsible. A review and appraisal of the literature associating a multidisciplinary perioperative team training intervention with patient safety outcomes of morbidity and mortality bring attention to the benefits of team training. The importance of a collaborative approach to perioperative patient safety is highlighted to motivate healthcare professionals to engage with enhancing a collective perioperative safety culture. Enhancing perioperative patient safety also requires a multifocal approach and collective commitment to a patient safety culture. Collaborative practice and its challenges in the context of the perioperative setting are explored, followed by a review and evaluation of the literature measuring an association between a team training intervention and patient safety. Implications of findings to practice are discussed, whereas Wenger’s Communities of Practice (CsOP) and Gittell’s Relational Coordination (RC) theories offer innovative perspectives to understand team potential. Considerations for further enhancing a collective perioperative safety culture are also provided.